2000
DOI: 10.1111/j.1095-8312.2000.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation of chewing lice (Insecta: Phthiraptera) from different skua taxa

Abstract: The licc, Haffneria grandis and Saemundssonia were extracted from their hosts, skuas (Aves: Stercorariidae). Lice werr extracted from dead birds by combing feathers, while lice from live birds were extracted using a delousing chamber containing chloroform vapour. Lice were measured and the data analyscd by canonical discriminant analysis. Lice show variation in morphology that is useful in identifying some of these hosts. This variation is presumably due to micro-environmental pressure providcd by each host. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In addition, the taxonomy may be problematic because morphological characters of lice are often conservative (Page et al, 2004). Several authors have suggested that only multivariate analysis can detect significant variations between related lice from different hosts (Ramli et al, 2000). However, morphologically identical species may be genetically different.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the taxonomy may be problematic because morphological characters of lice are often conservative (Page et al, 2004). Several authors have suggested that only multivariate analysis can detect significant variations between related lice from different hosts (Ramli et al, 2000). However, morphologically identical species may be genetically different.…”
Section: Discussionmentioning
confidence: 99%